Mechanical properties and structures of bulk nanomaterials based on carbon nanopolymorphs - Baimova, Julia A. (2014)
Bulk nanomaterials based on sp2 carbon nanopolymorphs are promising candidates for supercapacitors due to their unique properties such as extremely high specific surface area, high conductivity and stability against graphitization. However, the mechanical response of such materials to external loading is not understood well. This Letter studies the effect of hydrostatic pressure on the mechanical properties and structures of these materials via molecular dynamics simulations. Three types of nanopolymorphs-based nanomaterials that are composed of bended graphene flakes, short carbon nanotubes and fullerenes are considered. It is found that these three materials show a distinct relation between the pressure and volume strain. Moreover, their resistance to graphitization depends on the structure of their constituent components. The phenomena are explained by analysing the radial distribution function and coordination numbers of the atoms.